The Oxford handbook of cognitive literary studies - Zunshine, Lisa, 1968- (Oxford handbooks online, 2015)
This title considers how the architecture that enables human cognitive processing interacts with cultural and historical contexts. Organised into five parts (Narrative, History, and Imagination; Emotions and Empathy; The New Unconscious; Empirical and Qualitative Studies of Literature; and Cognitive Theory and Literary Experience), the volume considers case studies from a wide range of historical periods and national literary traditions.